Analysis of Tourism and Cultural Promotion of Local Communities in Increasing Tourist Visits in Baubau City, Southeast Sulawesi Province - Sartika Sartika; Bakhtiar Abbas; Nofal Supriaddin (PT. Hafasy Dwi Nawasena, 2025)
This study aims to analyze (1) Tourism promotion in increasing tourist visits in Baubau City; (2) The cultural program of the local community in Baubau City in increasing tourist visits; and (3) The impact of tourist visits in Baubau City. The informants in this study were five people. The analysis tool used is the Analysis Interactive Model from Miles and Huberman, which divides the steps in data analysis activities into several parts, namely data collection, data reduction, data display, and conclusion or verification. Based on the results of the study, it can be concluded that (1) Tourism promotion using advertising, sales promotion, personal selling, and personal selling can increase tourist visits in Baubau City; (2) The culture of the local community as assessed from technological tools, economic system, family system, and political power system can increase tourist visits in Baubau City; and (3) Tourist visits assessed from the increase in foreign and domestic visitor arrivals, increase in foreign exchange income from the tourism sector, expansion of employment, increase in the contribution of the tourism sector to GDP/GDP and increase tourism competitiveness in Baubau City have a good impact on the people of Baubau City.